Bubbles - Chase, Kit (New York, NY : G. P. Putnam's Sons, 2018)
"Kangaroo and Koala become fast friends when they vanquish a bubble monster together"--
Keywords: Bubbles -- Fiction; Kangaroos -- Fiction; Koala -- Fiction; Friendship -- Fiction; Bashfulness -- Fiction